2018
DOI: 10.1002/2017jd027124
|View full text |Cite
|
Sign up to set email alerts
|

Physical Interpretation of Mixing Diagrams

Abstract: Type of mixing at cloud edges is often determined by means of mixing diagrams showing the dependence of normalized cube of the mean volume radius on the dilution level. The mixing diagrams correspond to the final equilibrium state of mixing between two air volumes. While interpreting in situ measurements, scattering diagrams are plotted in which normalized droplet concentration is used instead of dilution level. Utilization of such scattering diagrams for interpretation of in situ observations faces significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the present study as well as in Pt3 and modeling studies performed by Andrejczuk et al (2006Andrejczuk et al ( , 2009 and Khain et al (2018), it is shown that time needed to establish equilibrium is either quite long or even never reached. This means that the scattering diagrams observed in situ are just snapshots of the transient mixing process.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the present study as well as in Pt3 and modeling studies performed by Andrejczuk et al (2006Andrejczuk et al ( , 2009 and Khain et al (2018), it is shown that time needed to establish equilibrium is either quite long or even never reached. This means that the scattering diagrams observed in situ are just snapshots of the transient mixing process.…”
Section: Discussionmentioning
confidence: 89%
“…At the same time, scattering diagrams may contain useful information concerning intensity of mixing, the DSD width and other parameters of DSDs (see Khain et al, 2018 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, our general conclusion is that the simplifications underlying the classical concept of mixing are too crude, making it impossible to use scattering diagrams for comprehensive analysis of mixing and especially for determination of mixing types. At the same time, scattering diagrams may contain useful information concerning intensity of mixing, the DSD width and other parameters of DSDs (see Khain et al, 2018…”
Section: Discussionmentioning
confidence: 99%
“…The effects of mixing of cloudy air with surrounding dry air on cloud microphysics are still the focus of many studies (see overview by Devenish et al, 2012). Processes of mixing are investigated in observations (Yum et al, 2015;Bera at al., 2016a, b), large eddy simulations (Andrejczuk et al, 2009;Khain et al, 2018) and direct numerical simulations (Kumar et al, 2014(Kumar et al, , 2017. Processes of mixing and their effects on droplet size distributions were recently investigated in a set of theoretical studies (Yang et al, 2016;Korolev et al, 2016 (hereafter, Pt1); Pinsky et al, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%